2017
DOI: 10.1038/ncomms14449
|View full text |Cite
|
Sign up to set email alerts
|

Usp9x regulates Ets-1 ubiquitination and stability to control NRAS expression and tumorigenicity in melanoma

Abstract: ETS transcription factors are commonly deregulated in cancer by chromosomal translocation, overexpression or post-translational modification to induce gene expression programs essential in tumorigenicity. Targeted destruction of these proteins may have therapeutic impact. Here we report that Ets-1 destruction is regulated by the deubiquitinating enzyme, Usp9x, and has major impact on the tumorigenic program of metastatic melanoma. Ets-1 deubiquitination blocks its proteasomal destruction and enhances tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 63 publications
3
67
0
Order By: Relevance
“…19,36,37 For example, elevated expression of USP9X has been documented in several types of human cancers, including non-small-cell lung cancer, esophageal squamous cell carcinoma, B-cell lymphoma, cervical carcinoma, and melanoma, and its high expression is closely linked with tumor growth, invasion, metastasis, and chemoresistance. 26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer.…”
Section: Discussionmentioning
confidence: 99%
“…19,36,37 For example, elevated expression of USP9X has been documented in several types of human cancers, including non-small-cell lung cancer, esophageal squamous cell carcinoma, B-cell lymphoma, cervical carcinoma, and melanoma, and its high expression is closely linked with tumor growth, invasion, metastasis, and chemoresistance. 26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin‐specific peptidase 9X (USP9X) is a highly conserved DUB belonging to the ubiquitin‐specific protease (USP) family . Accumulating evidence shows that USP9X is frequently upregulated and promotes tumorigenesis and chemoresistance in some types of human cancer, such as breast and lung cancer, melanoma, lymphoma, and glioblastoma . Strikingly, a tumor suppressor role of USP9X has been documented in pancreatic, colorectal, and renal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…can play a dual role in cancers, promoting or suppressing tumor development, depending on the cancer type and disease model studied. For example, by stabilizing MCL1, USP9x can promote cancer cell survival or confer radioresistance in B-cell acute lymphoblastic leukemia (Zhou et al, 2015), non-small-cell lung cancer (Yan et al, 2014) breast and melanoma (Potu et al, 2017a). However, in pancreatic ductal adenocarcinoma, loss of USP9x enhances transformation and protects pancreatic cancer cells from apoptosis (Perez-Mancera et al, 2012).…”
Section: Introductionmentioning
confidence: 99%